Approach to direct coning/sculling error compensation based on the sinusoidal modelling of IMU signal. Issue 5 (1st June 2013) - Kang, Chul Woo; Ik Cho, Nam; Park, Chan Gook
Abstract : A direct coning mitigation algorithm based on the detection of a sinusoidal component in the gyro measurements is proposed. The coning error, which is one of dominant error sources affecting the accuracy of attitude computation in the inertial navigation system (INS), is induced by the sinusoidal motion such as a manoeuvre of vehicle or the vibration of a dithering of ring laser gyro. However, many researchers have developed coning error mitigation algorithms based on the higher‐order polynomial model and its correction terms are extracted from the gyro output without faithful consideration of the periodicity of motion. Hence, the authors first detect and estimate the sinusoidal components from gyro measurements, and then find the higher‐order correction terms from the estimated sinusoidal parameters. The authors also show that this algorithm can be applied to the mitigation of sculling error because of its duality to the coning motion. Simulation results show that the direct compensation algorithm works effectively for the navigation of vehicles with continuous and steady oscillations. Also, the rate table test with HG1700 inertial measurement unit (IMU) is conducted to show the effectiveness of proposed algorithm on real INS signal.